2021
DOI: 10.1155/2021/1186458
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Hypomethylation of DOCK1 Leading to High Expression Correlates with Neurologic Deterioration and Poor Function Outcomes after Spontaneous Intracerebral Hemorrhage

Abstract: Objective. Spontaneous intracerebral hemorrhage (ICH) is a blood clot arising in the brain parenchyma in the absence of trauma or surgery and accounts for 10% to 15% of all strokes, leading to higher rates of mortality and morbidity than either ischemic stroke or subarachnoid hemorrhage. We sought to investigate the potential association of DOCK1 with neurological deficits and outcomes in patients with spontaneous ICH. Methods. Identification of methylation-regulated differentially expressed genes (MeDEGs) bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…At admission, data collected included the patients’ age, gender, Body Mass Index (BMI), time of onset to emergency department (ED), SBP on admission, diastolic blood pressure (DBP) on admission, body temperature, baseline hematoma volume, history of high blood pressure (HBP), smoking history, drinking history, other medical history, serum sodium, serum calcium, hemoglobin (Hb), white blood cell (WBC) count, platelet (PLT) count, activated partial thromboplastin time, international normalized ratio (INR), fibrous protein, blood glucose, serum creatinine, troponin, total cholesterol (TCHO), low-density lipoprotein cholesterin (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglyceride (TG), bleeding part, IVH, IVH expansion, subarachnoid expansion, DBP change in 24 h, SBP change in 24 h, hematoma volume change in 24 h, blend sign, spot sign, leukodystrophy, lacuna cerebri, and brain atrophy (any central or cortical reduction). The hematoma volume was calculated according to the Coniglobus formula ( 19 ): V = a × b × c × 1/2 (where a represents the longest diameter of hematoma at the level of maximum hematoma area, b represents the longest diameter perpendicular to the longest diameter at the level of maximum hematoma area, and c represents the number of layers with bleeding in CT images). The proportion of missing values for most of the included variables was less than 7%, which were filled using multiple imputation.…”
Section: Methodsmentioning
confidence: 99%
“…At admission, data collected included the patients’ age, gender, Body Mass Index (BMI), time of onset to emergency department (ED), SBP on admission, diastolic blood pressure (DBP) on admission, body temperature, baseline hematoma volume, history of high blood pressure (HBP), smoking history, drinking history, other medical history, serum sodium, serum calcium, hemoglobin (Hb), white blood cell (WBC) count, platelet (PLT) count, activated partial thromboplastin time, international normalized ratio (INR), fibrous protein, blood glucose, serum creatinine, troponin, total cholesterol (TCHO), low-density lipoprotein cholesterin (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglyceride (TG), bleeding part, IVH, IVH expansion, subarachnoid expansion, DBP change in 24 h, SBP change in 24 h, hematoma volume change in 24 h, blend sign, spot sign, leukodystrophy, lacuna cerebri, and brain atrophy (any central or cortical reduction). The hematoma volume was calculated according to the Coniglobus formula ( 19 ): V = a × b × c × 1/2 (where a represents the longest diameter of hematoma at the level of maximum hematoma area, b represents the longest diameter perpendicular to the longest diameter at the level of maximum hematoma area, and c represents the number of layers with bleeding in CT images). The proportion of missing values for most of the included variables was less than 7%, which were filled using multiple imputation.…”
Section: Methodsmentioning
confidence: 99%
“…44 In patients with spontaneous ICH, hypomethylation of the dedicator of cytokinesis 1 (DOCK1) promoter was associated with increased DOCK1 expression, hematoma volume, and worsened rehabilitative outcomes. 45…”
Section: Epigenetic Mechanisms In Strokementioning
confidence: 99%
“…44 In patients with spontaneous ICH, hypomethylation of the dedicator of cytokinesis 1 (DOCK1) promoter was associated with increased DOCK1 expression, hematoma volume, and worsened rehabilitative outcomes. 45 In ischemic stroke patients, several studies showed significant correlation between blood DNA methylation and post-stroke outcome. In particular, blood methylation patterns in solute carrier family 6 member 4 (SLC6A4) have been associated with the risk of stroke recurrence, post-stroke depression, and neurologic deterioration.…”
Section: Stroke and Dna Methylationmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%